A diagnostic workup and laparoscopic approach for median arcuate ligament syndrome. Issue 7 (1st February 2022) - Diab, Jason; Diab, Vanessa; Berney, Christophe R
Abstract: Background: Median arcuate ligament syndrome (MALS) is a rare disorder characterized by the compression of the coeliac trunk and plexus by fibrous arches of the median ligament. It commonly occurs in young women with postprandial epigastric pain, weight loss and nausea. We present a single surgeon experience on the diagnostic approach and management of MALS with a focus on laparoscopic surgery. Methods: A retrospective review of adult patients diagnosed with MALS during a 10‐year period (2011–2021) was conducted at Bankstown‐Lidcombe hospital in New South Wales, Australia. Results: MALS was diagnosed in six patients (mean 46 years, range: 27–74 years old), all confirmed on mesenteric duplex ultrasound and computed tomography angiography. The most common presentations were women with post‐prandial pain, exercise induced pain and an average weight loss of 14.5 kg. The median interval from onset of symptoms to surgical referral was 10.5 months. The average BMI was 24.1 kg/m 2 and most had a grade III American Society of Anaesthesiologist physical status. All patients underwent laparoscopic release of median arcuate ligament with one patient requiring endovascular stenting. The mean operative time was 119 minutes with two minor post‐operative complications, but no mortalities. The median hospital length of stay was 3.5 days with a median follow up of 3.5 years. Conclusion: Laparoscopic median arcuate ligament release with endovascular support for selected cases provides sound clinical resolution of symptoms and long‐term results. Abstract : Median arcuate ligament syndrome (MALS) is a rare disorder characterised by the compression of the coeliac trunk and plexus by fibrous arches of the median ligament. It commonly occurs in young women with postprandial epigastric pain, weight loss and nausea, but is typically diagnosed after the exclusion of other common abdominal pathologies.